Pseudoaneurysm as a Late Complication of Chronic Stanford Type A Intramural Hematoma Requiring Endovascular Repair - Wayne H. Miller, MD; David Hsi, MD; Anna Koulova, MD; Andrey Vavrenyuk, MD; Isaac George, MD; Virendra Patel, MD; Hiroo Takayama, MD (JACC: Case Reports, 2020)
Aortic intramural hematoma accounts for 5% to 20% of patients with acute aortic syndrome. Endovascular grafts have evolved as minimally invasive alternatives for treatment in some highly selected patients. We present the case of a patient who had late complications of a chronic Stanford type A intramural hematoma requiring thoracic endovascular aortic repair. (Level of Difficulty: Beginner.)